Guide to facilitate a multi-actor theory of the change development process - Falk, Thomas; van Rooyen, Andre F.; Homann Kee Tui, Sabine; Zhang, Wei (International Crops Research Institute for the Semi-Arid Tropics, 2021)
It remains a critical challenge for researchers and practitioners to combine innovations and interventions in system changes to help achieve sustainable development goals. Ideally, theories of change establish this link by working backward from the outcomes to identify all of the conditions that must be in place for the desired change to occur. In practice, theories of change are often developed looking forward by formulating a story about the way an intervention that is considered effective based upon a plausible claim, leads to outcomes. In either case, theories of change are based upon assumptions that are in many ways implicit and not transparent. For instance, assumptions about why and which actors need to change which behavior and what drives their behavioral changes are critical. This highlights the importance of reflecting on the steps taken when creating outputs to achieve outcomes. This guide intends to help intervention and process designers and decision makers develop robust, fair, effective, efficient, and sustainable theories of change.